2020
DOI: 10.1111/jcpp.13273
|View full text |Cite
|
Sign up to set email alerts
|

Higher aggression is related to poorer academic performance in compulsory education

Abstract: Background: To conduct a comprehensive assessment of the association between aggression and academic performance in compulsory education. Method: We studied aggression and academic performance in over 27,000 individuals from four European twin cohorts participating in the ACTION consortium (Aggression in Children: Unraveling gene-environment interplay to inform Treatment and InterventiON strategies). Individual level data on aggression at ages 7-16 were assessed by three instruments (Achenbach System of Empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Furthermore, both the ASEBA system (of which the TRF is a part) and the SDQ were assessed by Achenbach et al (2008) and generally found to produce comparable results across countries, with more variation found within populations than between. Moreover, we have found that the negative relationship between aggression and academic performance was consistent and generally similar in ACTION cohorts with different aggression questionnaires (Vuoksimaa, 2020 in press).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, both the ASEBA system (of which the TRF is a part) and the SDQ were assessed by Achenbach et al (2008) and generally found to produce comparable results across countries, with more variation found within populations than between. Moreover, we have found that the negative relationship between aggression and academic performance was consistent and generally similar in ACTION cohorts with different aggression questionnaires (Vuoksimaa, 2020 in press).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, both the ASEBA system (of which the TRF is a part) and the SDQ were assessed by Achenbach et al [52] and generally found to produce comparable results across countries, with more variation found within populations than between. Moreover, in ACTION consortium analyses, the SDQ and CBCL (parent version of the ASEBA questionnaire family of which the TRF is a part) aggression scales were found to capture the same underlying genetic aspects of aggression [53], despite item-level differences, and the negative relationship between aggression and academic performance was consistent and generally similar in FT12, NTR and TEDS cohorts using teacher-rated MPNI, SDQ, and TRF [54].…”
Section: Plos Onementioning
confidence: 94%
“…Aggressive behaviour is a common symptom of childhood psychopathology and linked to lower academic performance and social functioning [1], crime involvement [2], substance use [3], and lower earnings [4].…”
Section: Polygenic Risk For Aggressive Behaviour From Late Childhood mentioning
confidence: 99%
“…We first examined pairwise correlations between PRSAGG and parent-, self-, and teacher-reported aggressive behaviour across all waves. Second, we fit latent class growth models 1 of aggressive behaviour based on parent- 1 We computed growth mixture models (which allow for within-class variance) and latent class growth models (which restrict within-group variance of intercept and slope to zero) with the aim to compare model fit between both types. However, GMM did not converge in all cases, owing to non-positive covariance matrices.…”
Section: Analytic Strategymentioning
confidence: 99%